Canteen Wastewater and Gray Water Treatment Using Subsurface Constructed Wetland-Multilayer Filtration Vertical Flow Type with Melati Air (Echindorus paleafolius) - Ariani Dwi Astuti; Astri Rinanti; Alexandre Amo F. Viera (Graduate Program of Syiah Kuala University, 2017)
Domestic wastewater needs to be treated because it can pollute the environment, either water bodies, ground water, or soil. One alternative to treat domestic wastewater is using subsurface constructed wetland methods. This method has advantages, among others, cheap, simple technology and can be applied to the area of ample land. In this research, subsurface contructed wetlands-multilayer filtration with vertical flow type using Melati Air (Echindorus paleafolius) in field scale to treat domestic wastewater from canteens and gray water toilet of Senior High School at Bekasi with treatment capacity for 2261 L/day. Subsurface constructed wetlands-multilayer filtration with vertical flow type is an advanced treatment in this research. For preliminary treatment the collecting and aeration tank is used. Performance of subsurface constructed wetland-multilayer filtration with vertical flow type was able to achieve effluent COD parameters of 40 mg / L (standard 100 mg/L) from an average influent of 350 mg/L with removal efficiency of 90%, while BOD was successfully degraded to 33.00 mg/L (quality standard 30 mg/L) of an average influent concentration of 350 mg/L. In addition, the parameters analyzed are total nitrogen, the total phosphate succeeded to meet the quality standard. Based on the results of laboratory analysis, the reactor is able to treat organic loading of 500-700 kg BOD5/Ha/Day compared to previous research which is range from 40-300 kg BOD/Ha/ Day. Similarly, the value of K in this study ranged from 0.35-0.57 m/day for BOD and 0.37-0.45 m/day for COD compared to precious research which is 0.055-0.16 m / day for BOD and 0.027-0.16 m / day for COD.